The Effect of Product, Price, Location, and Promotion on Consumer Interest - Hariadi, Sam; Suwanti, S.; Amalia, A. (Manunggal Halim Jaya, 2024)
Marketing strategy consists of 4P integrated marketing elements (product, price, promotion, place), which constantly evolve in line with the movement of the company changes in the marketing environment and the collapse of consumer behavior. Consumer behavior has vast implications for the formulation of marketing strategies. This is because marketing strategy involves two main activities: selecting the market to be targeted for marketing and formulating and compiling the right marketing mix combination so that consumer needs can be met satisfactorily. A product is an item offered to the market for attention. It is owned, used, or consumed and can satisfy consumer needs. One of marketing management's main tasks and responsibilities is to think about product design; the products made are products that consumers need. Opon Drinks also produces packaged coffee, which has a taste that is not very different from that of packaged coffee.